Female representation at the national level and women sport volunteering in European countries - Katrin Scharfenkamp; Pamela Wicker; Bernd Frick (Nonprofit Management and Leadership, 2023)
This study examines the moderating effects of national female labor force participation, women in sport leadership positions, and female medalists in recent Olympic Games on women's probability to volunteer in sport. Based on social role theory and the similarity attraction paradigm, we predict that all three factors result in a higher probability of women to volunteer in sport, but with differences among age groups. Linear probability models before and after applying coarsened exact matching were estimated using data from the 2017 Eurobarometer (n~=~18,529). The results show that women have a significantly lower probability to volunteer in sport in countries with high female labor force participation and a high share of women in leadership positions in sport organizations. The likelihood of women volunteering in sport is significantly higher in countries with a high share of female Olympic medalists. The age group-specific analysis asking whether volunteering should be considered an investment in human capital by younger women and/or an acquisition of social capital by older women, reveals that a high presence of women among leaders in sport organizations and Olympic medalists is significantly positively correlated with the probability for young women to volunteer in sport. Managers and leaders of nonprofit sport organizations learn from our study that volunteering should be perceived as an investment in human capital by younger women rather than an attempt to acquire social capital by older women.
Keywords: 650; employee generations; leadership; nonprofit organizations; social roles; sport volunteering; women